Blanching effect on the quality and shelf life of pea - Pervin, Shahnaj; Miaruddin, Md; Islam, Md Serazul; Khan, Md Hafizul Haque; Rahman, Md Mizanur (Journal of Postharvest Technology, 2024)
The effects of blanching on the peas were investigated to determine the quality and shelf life of the pea during storage in deep freeze for six months. The experiment was carried out Completely Randomized Design and there were five treatments using four different blanching times as 1 min, 3min, 5 min, and 7 min with fixed temperature of 800C. The data were analyzed under computerized statistical methods of M-stat and Duncan’s Multiple Range Test was used to compare the means. The chemical compositions were analyzed and the following results were investigated: the dry matter percentages were slightly decreased over storage duration. The acidity contents of blanching peas were slightly decreased and PHcontents slightly increased on storage. The Vitamin C and β-carotene contents were decreased after increasing the blanching time. Peroxidase and catalase inactivation time of enzyme for blanching of peas represents the most enzymes were inactivated rapidly as temperature rises to 80OC with 7 minutes blanching. Therefore, the study results showed that the frozen peas were stored well in home deep freeze up to four months blanching at 800C for 7 minutes.